2018
DOI: 10.1186/s12944-018-0833-2
|View full text |Cite
|
Sign up to set email alerts
|

New insights into apolipoprotein A5 in controlling lipoprotein metabolism in obesity and the metabolic syndrome patients

Abstract: Apolipoprotein A5 (apoA5) has been identified to play an important role in lipid metabolism, specifically in triglyceride (TG) and TG-rich lipoproteins (TRLs) metabolism. Numerous evidence has demonstrated for an association between apoA5 and the increased risk of obesity and metabolic syndrome, but the mechanism remains to be fully elucidated. Recently, several studies verified that apoA5 could significantly reduce plasma TG level by stimulating lipoprotein lipase (LPL) activity, and the intracellular role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 84 publications
2
41
0
1
Order By: Relevance
“…ZNF259_rs2160669 has been shown to have an association with serum HDL-cholesterol and TAG concentrations. The APOA5 in the present study has been reported to be involved in the regulation of lipoprotein metabolism in obese and the MetS patients in a number of studies (21) , and APOA5_rs651821 is also associated with the MetS and metabolic components in Asian populations (22,23) . The EFCAB4B gene has been linked to the development of non-alcoholic fatty liver diseases (24) .…”
Section: Discussionsupporting
confidence: 54%
“…ZNF259_rs2160669 has been shown to have an association with serum HDL-cholesterol and TAG concentrations. The APOA5 in the present study has been reported to be involved in the regulation of lipoprotein metabolism in obese and the MetS patients in a number of studies (21) , and APOA5_rs651821 is also associated with the MetS and metabolic components in Asian populations (22,23) . The EFCAB4B gene has been linked to the development of non-alcoholic fatty liver diseases (24) .…”
Section: Discussionsupporting
confidence: 54%
“…Although APOA5 is the last discovered member of the apolipoprotein APOA1/C3/A4 gene cluster, the important function of the APOA5 gene for lipid metabolism has been demonstrated by transgenic and knockout models (Hubáček et al, 2009). Apo A‐V plays an important role in activation of LPL (binds to and enhances the activity of LPL) (Hubáček et al, 2009; Su et al, 2018). In addition, recombinant APOA5 interacts with high affinity to the LDL receptor family members (Dorfmeister et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The major functions of LPL are to catalyze the decomposition of chylomicrons (CM) and very-low-density lipoproteins (VLDL) to TG and free fatty acids, and to promote the transport of protein, phospholipid, and apolipoprotein. As a consequence, the level of HDL is increased, and the high level of TG is suppressed in obesity [41]. A previous study has shown that a decrease in LPL activity may result in the reduced decomposition of TG-rich VLDL and CM, slow clearance rate, increased plasma TG levels, and inhibited HDL-C formation, thus leading to hypertriglyceridemia, low HDL-C level and, ultimately, obesity [42].…”
Section: Discussionmentioning
confidence: 99%